2022
DOI: 10.1093/jscr/rjac564
|View full text |Cite
|
Sign up to set email alerts
|

Fatal sepsis from appendicitis caused by an impacted tooth

Abstract: Acute appendicitis is one of the most common causes of acute abdominal pain globally. The pathophysiology of acute appendicitis is due to occlusion of the appendiceal lumen commonly from a faecolith. Obstruction of the appendiceal lumen by ingested foreign bodies is possible albeit rare. Here, we present an extremely rare case of acute appendicitis caused by impaction of the patients tooth within the lumen of the appendix. There have been only seven reported cases of impacted teeth causing appendicitis in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Foreign bodies as a possible cause of acute appendicitis have been described in several recent studies (most commonly part of bone or toothpick). Other less common foreign bodies such as earrings, needles, and dental objects have been described [23,24,27,[30][31][32]. A recent study describes how a detailed history revealed that the patient had swallowed a dental crown.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies as a possible cause of acute appendicitis have been described in several recent studies (most commonly part of bone or toothpick). Other less common foreign bodies such as earrings, needles, and dental objects have been described [23,24,27,[30][31][32]. A recent study describes how a detailed history revealed that the patient had swallowed a dental crown.…”
Section: Discussionmentioning
confidence: 99%